2020
DOI: 10.1111/cbdd.13748
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of C3 substituted chalcone‐based derivatives of 7‐azaindole as protein kinase inhibitors

Abstract: Chalcones are a group of naturally occurring or synthetic compounds which possess a wide range of biological activities. In this paper, a series of twenty-three 7-azaindole-chalcone hybrids (5a-w) were synthesized and evaluated as potential protein kinase inhibitors. Analyses of structure-activity relationships revealed that some of these compounds exhibit significant activity against Haspin kinase, with compounds 5f and 5q exhibiting IC 50 values of 0.47 and 0.41 µM, respectively. Furthermore, 5f also inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[23][24][25] Its synthetically designed derivatives have been employed as potential protein kinase inhibitors which are important drug targets in various oncology studies. [26][27][28][29][30] The molecules have also been utilized in the design of antitumor, anti-inflammatory, antibacterial, antimalarial, antimicrobial, antifungal, antituberculosis, and anticancer agents. [31][32][33][34][35][36] Recent studies have shown that Janus Kinase (JAK) inhibitors, such as Peficitinib, containing an azaindole moiety, have shown promising results in COVID-19 treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Its synthetically designed derivatives have been employed as potential protein kinase inhibitors which are important drug targets in various oncology studies. [26][27][28][29][30] The molecules have also been utilized in the design of antitumor, anti-inflammatory, antibacterial, antimalarial, antimicrobial, antifungal, antituberculosis, and anticancer agents. [31][32][33][34][35][36] Recent studies have shown that Janus Kinase (JAK) inhibitors, such as Peficitinib, containing an azaindole moiety, have shown promising results in COVID-19 treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Its synthetically designed derivatives have been employed as potential protein kinase inhibitors which are important drug targets in various oncology studies. [26][27][28] They work as an excellent coronary vasodilator and hypotensive agents. 29,30 They are also utilized in the designing of antitumor, antiinflammatory, antibacterial, antimalarial, antimicrobial, antifungal, antituberculosis, and anticancer properties.…”
Section: Introductionmentioning
confidence: 99%